PHACTR1 modulates vascular compliance but not endothelial function: a translational study. Issue 2 (2nd June 2022) - Wood, Alice; Antonopoulos, Alexios; Chuaiphichai, Surawee; Kyriakou, Theodosios; Diaz, Rebeca; Al Hussaini, Abtehale; Marsh, Anna-Marie; Sian, Manjit; Meisuria, Mitul; McCann, Gerry; Rashbrook, Victoria S; Drydale, Edward; et al.
Abstract: Aims: The non-coding locus at 6p24 located in Intron 3 of PHACTR1 has consistently been implicated as a risk allele in myocardial infarction and multiple other vascular diseases. Recent murine studies have identified a role for Phactr1 in the development of atherosclerosis. However, the role of PHACTR1 in vascular tone and in vivo vascular remodelling has yet to be established. The aim of this study was to investigate the role of PHACTR1 in vascular function. Methods and results: Prospectively recruited coronary artery disease (CAD) patients undergoing bypass surgery and retrospectively recruited spontaneous coronary artery dissection (SCAD) patients and matched healthy volunteers were genotyped at the PHACTR1 rs9349379 locus. We observed a significant association between the PHACTR1 loci and changes in distensibility in both the ascending aorta (AA = 0.0053 ± 0.0004, AG = 0.0041 ± 0.003, GG = 0.0034 ± 0.0009, P < 0.05, n = 58, 54, and 7, respectively) and carotid artery (AA = 12.83 ± 0.51, AG = 11.14 ± 0.38, GG = 11.69 ± 0.66, P < 0.05, n = 70, 65, and 18, respectively). This association was not observed in the descending aorta or in SCAD patients. In contrast, the PHACTR1 locus was not associated with changes in endothelial cell function with no association between the rs9349379 locus and in vivo or ex vivo vascular function observed in CAD patients. This finding was confirmed in our murine model where the loss of Phactr1 on the pro-atherosclerosis ApoE −/− background did not alter ex vivo vascular function. Conclusion: In conclusion, we have shown a role for PHACTR1 in arterial compliance across multiple vascular beds. Our study suggests that PHACTR1 has a key structural role within the vasculature. Graphical Abstract: Graphical abstract